Peningkatan Kemampuan Menulis Puisi Rakyat Menggunakan Pendekatan Culturally Responsive Teaching Pada Peserta Didik Kelas VII-9 SMP Negeri 11 Medan - Ilham Ruser; Syamsuyurnita Syamsuyurnita; Rizal Manurung (Concept: Journal of Social Humanities and Education, 2023)
This classroom action research was motivated by the low ability of students in class VII-9 at SMP Negeri 11 Medan in writing folk poetry as evidenced by the results of the task of writing rhymes, the grades achieved by students in class VII-9 were still low. Only a few reached the minimum completeness criteria. The less than optimal student scores are due to several obstacles that arise from the students themselves. These obstacles are students having difficulty determining and finding ideas, having difficulty developing ideas that have been obtained in the form of rhymes due to lack of vocabulary mastery, and students who are not used to expressing their thoughts or imagination in the form of poetry. This research was conducted to investigate whether the Culturally Responsive Teaching approach was effective in improving the skills of writing folk poetry in class VII-9 students of SMP Negeri 11 Medan. The CRT approach used in research aims to improve the skills of writing folk poetry so that students are able to understand folk poetry and are able to write folk poetry well. The results of data analysis showed an increase from cycle I to cycle II. This can be seen from the average value of students in each cycle. The average score of the students in the first cycle was 69.06 in the less category, while the average score of the students in the second cycle was 78.75 in the good category.